2015
DOI: 10.1074/jbc.m114.604454
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Structural Analysis of a Bifunctional Cellulase/Xylanase from Clostridium thermocellum

Abstract: Background: CtCel5E can degrade both cellulose and hemicellulose (xylan). Results: X-ray crystallography and site-directed mutagenesis were used to assess the roles of the active-site residues in CtCel5E. Conclusion: A flexible loop and other residues participate in substrate discrimination. Significance: This study provides the mechanisms of substrate recognition and a blueprint for engineering CtCel5E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Apparently, when comparing the kinetic ratios (that is, V max /K m ) of cellulases with those of xylanases within a single organism, it emerged from our work that the ratios of cellulases were always higher than those of xylanases for all the obtained fungal isolates as described in Figure 5 and Table 3. This scenario is not unusual because previously, a recombinant protein from Clostridium thermocellum, CtCel5E, that had a dual function as a cellulase and xylanase, displayed a K m value of 2.1 mM and a V max of 1 564 µmol/s for the cellulase and a K m value of 4.6 mM and a V max of 883.5 µmol/s for the xylanase (Yuan et al, 2015). Notably, all the kinetic values of CtCel5E together with most of those proteins in Tables 5 and 6 were generally lower than those of our own enzyme extracts probably due to three possible reasons.…”
Section: Most Studies Nowadays Have Focused On Cellulases Andmentioning
confidence: 90%
“…Apparently, when comparing the kinetic ratios (that is, V max /K m ) of cellulases with those of xylanases within a single organism, it emerged from our work that the ratios of cellulases were always higher than those of xylanases for all the obtained fungal isolates as described in Figure 5 and Table 3. This scenario is not unusual because previously, a recombinant protein from Clostridium thermocellum, CtCel5E, that had a dual function as a cellulase and xylanase, displayed a K m value of 2.1 mM and a V max of 1 564 µmol/s for the cellulase and a K m value of 4.6 mM and a V max of 883.5 µmol/s for the xylanase (Yuan et al, 2015). Notably, all the kinetic values of CtCel5E together with most of those proteins in Tables 5 and 6 were generally lower than those of our own enzyme extracts probably due to three possible reasons.…”
Section: Most Studies Nowadays Have Focused On Cellulases Andmentioning
confidence: 90%
“…Park et al (2014) reported 23-fold glucose production enhancement over that of free enzymes after their investigation of the effects of localization, surface accessibility, and functionality of synergetic enzymes on Scaf3-decorated bacteria outer membrane vesicles (OMVs) using phosphoric acid-swollen cellulose (PASC) as substrate. Yuan et al (2015), in an investigation to biochemically characterize and structurally analyze cellulase/xylanase from Clostridium thermocellum, also revealed equally insightful results. Advancement in cellulosome investigation has led to the advent of its artificial counterpart, called designer cellulosomes, described below.…”
Section: Cell-surface Display Systemsmentioning
confidence: 96%
“…On account of the obvious benefits reported in the literature, scientists have consistently investigated the gene (Yagüe et al 1990;Zverlov et al 2003;Koeck et al 2013), fusion/modification of enzymes (Ciolacu et al 2010;Lee et al 2010;Ye et al 2010;Lee et al 2011;Nakashima et al 2014), and the optimal growth (Islam et al 2013;Reed et al 2014) of these useful microbes to harness their inherent benefits. For example, the biochemical and biophysical characteristics of multimodular enzymes from Clostridium thermocellum (Zverlov et al 2005;Tachaapaikoon et al 2012;Brunecky et al 2012;Hirano et al 2013;Yuan et al 2015) and Thermotoga maritima (Chhabra et al 2002;Carvalho et al 2004;Pereira et al 2010;Wu et al 2011) have been reported.…”
Section: Bacteria Sourcesmentioning
confidence: 99%
“…6,7 Progress in this field has seen the application of cell-free (crude extract), [8][9][10] immobilized [11][12][13] and microbial surface-displayed cellulases. [14][15][16] The cell-free form is the most common among the three categories. Recently, there has been a gradual shift towards the cell surface-display technology owing to its relatively cheaper production cost and reusability potential.…”
Section: Introductionmentioning
confidence: 99%